The effect on the seasonal dynamics of soil N transformation resulting from biochar application in karst mountains - Wang, Hankun; Liu, Junping; Wu, Yongbo; Xue, Jianhui (Frontiers in Ecology and Evolution, 2023)
Nitrogen (N) is frequently a limiting element for primary productivity in karst ecosystems due to its low availability. N mineralization drives N availability and is important for improving N use efficiency in soils. While the use of biochar in agricultural and forest ecosystems has attracted great attention recently, little has been reported on the seasonal dynamics of soil N transformation in karst and its response to biochar application. Therefore, we conducted a pot experiment over 1 year using two types of biochar (rice husk biochar and wood biochar) as soil amendments. The results demonstrated that in the karst mountain region, the soil had the highest content of mineral N (19.41 mg/kg) during summer and the lowest content of mineral nitrogen (3.74 mg/kg) during winter. There was a significant positive correlation (p<0.01) between soil mineral N content and temperature, and between soil temperature and urease activity. Thus, the higher temperatures during summer enhance soil urease activity, making it easier for soil N mineralization to occur, and increasing soil mineral N content. The soil mineral N content of the CK treatment was 2.61% to 209.42% higher than the other treatments, indicating that the biochar application reduced the soil mineral N content, which was supported by the negative net N mineralization. This may be due to biochar facilitating the adsorption and immobilization of nitrogen. The soil mineral N content of rice husk biochar was significantly higher than that of woody biochar by 109.55%, indicating that woody biochar would adsorb more N or more readily stimulate N immobilization than rice husk biochar. Furthermore, soil N immobilization (negative net N mineralization) after biochar application varied according to the season. The higher temperatures during summer promoted soil N immobilization more with biochar application. These results are crucial to understanding soil N transformation in karst mountains and guiding effective soil management.